MEASURING THE PERFORMANCE OF ISLAMIC BANKS THROUGH RISK PROFILE, EARNING, AND CAPITAL - Bambang Iswanto; Angrum Pratiwi; Idhafiyyah Anwar (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2023)
The emergence of COVID-19 as a global pandemic has impacted slowing economic growth, which has also affected regional financial and banking stability in East Kalimantan. This study aims to describe the results of measuring the performance of Islamic Commercial Banks using the risk profile, earning & capital method. The research population is Islamic banks operating in the Samarinda area of ​​East Kalimantan, and the research sample selection is purposive sampling. The study results show that the measurement in terms of the risk profile aspect shows an average rating of 2, "Good," and 3, "Fair enough." While the average rating on the FDR ratio is rated 2, "Good," a rating of 3 is "Enough Good," and a rating of 1 is "Very Good." Furthermore, in terms of earning assessment, by looking at the ROA, ROE, and BOPO ratios after being ranked, the results show that ROE and BOPO ratios rank 4 and 5. In contrast, NOM is rated 1, while the ROA ratio continues to fluctuate from rank 1 to rank 5, meaning that bank performance Sharia law differs in generating returns on assets. This is a note, as well as opportunities and challenges for banks to be able to compete with other banks. Furthermore, capital assessment is rated "Very Good," which means that it has met the standards set by Bank Indonesia and the Financial Services Authority.